2019
DOI: 10.1111/pde.13898
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic care of sexual and gender minority/LGBTQIA youth, Part 2: Recognition and management of the unique dermatologic needs of SGM adolescents

Abstract: Sexual and gender minority (SGM) individuals, including lesbian, gay, bisexual, transgender/gender diverse, questioning/queer, intersex, and asexual (LGBTQIA) persons, represent a historically underserved population within the field of medicine, though their unique health needs are increasingly recognized. Part 2 of this two‐part review will address unique concerns regarding acne, tanning behavior, sexually transmitted infections, and other health disparities among SGM adolescents. A more comprehensive underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…In recent years, our group has treated 12 transgender adolescent boys for whom masculinizing treatment with testosterone either caused new‐onset acne or worsened pre‐existing acne 3 . Four of the 12 patients required treatment with isotretinoin (Table 1), which for two patients had to be suspended owing to the appearance of clinical depression and attempts to cause self‐harm.…”
Section: Patient Age  Years Dose Of Isotretinoin Mg/day Duration Ofmentioning
confidence: 99%
“…In recent years, our group has treated 12 transgender adolescent boys for whom masculinizing treatment with testosterone either caused new‐onset acne or worsened pre‐existing acne 3 . Four of the 12 patients required treatment with isotretinoin (Table 1), which for two patients had to be suspended owing to the appearance of clinical depression and attempts to cause self‐harm.…”
Section: Patient Age  Years Dose Of Isotretinoin Mg/day Duration Ofmentioning
confidence: 99%
“…The HPV vaccination rate among MSM in adolescent populations varies across reports. [5][6][7] Interestingly, a 2016 survey study found that MSM had approximately 2-times greater odds of initiating the HPV vaccine than heterosexual men. 8 However, a study specifically sampling young gay and bisexual men (N=428) found that only 13% had received any doses of the HPV vaccine.…”
Section: Barriers To Hpv Vaccine Administrationmentioning
confidence: 99%
“…[14][15][16] Dermatologic conditions important to the LGBTQ community currently include increased risk of skin cancer and indoor tanning in gay and bisexual men, acne and hair-related changes associated with hormone therapy in transgender persons, and increased risk for oral human papillomavirus (HPV) due to decreased rates of HPV vaccination in individuals who engage in same-sex sexual activity. [17][18][19] The Accreditation Council for Graduate Medical Education Competencies recognize the importance of LGBTQ health by requiring dermatology residents to demonstrate responsiveness in caring for LGBTQ populations 6 ; however, many dermatology residency programs still lack formal curricula. 20 Furthermore, no study has examined the efficacy of training in LGBTQ cultural responsiveness in dermatology.…”
Section: Introductionmentioning
confidence: 99%